Experimento em escala e comparação do desempenho de duas turbinas eólicas equipadas com difusor com diferentes ângulos de ataque - Macêdo, Carlos Henrique Silveira (2016)
One of the most promising concepts for increasing the efficiency of a wind turbine is the horizontal axis wind turbine equipped with an aerodynamic diffuser. The diffuser controls the expansion of the turbine exhaust flow, creating a low pressure area at the turbine exit. This increase in pressure difference induces a greater mass flow of air through the turbine when compared to a conventional turbine of the same diameter. Thus, this work proposes to design, build, test and compare the results obtained by one rotor in scale with a rotor system - diffuser. One rotor was designed and developed with tip speed ratio value 7. Rotor blades were chosen with length of 180 mm and aerodynamic airfoil NREL S809, based on the concepts of the blade element momentum (BEM). Two aerodynamic diffusers were built with NACA 4412, made of plywood and cut by laser, profiles with attack angles of 7º and 11º. They were filled with a polyurethane foam, covered with fiberglass tissue and subsequently a thermoplastic. The tests were performed in the Aerodynamics and Fluid Mechanics Laboratory of the Federal University of Ceará, where free flow velocity data, flow velocity with the rotor and the rotor system - diffuser in operation, as well as angular velocity measurements and torque generated by the blades were collected in order to know the power curve of each rotor and the rotor system - diffuser. It was possible to observe a maximum of 3.6% increase in power coefficient for the rotor equipped with the diffuser with attack angle of 7º and 4% with attack angle 11º for the intervals of λ = 6.2 to λ = 6.7. This power coefficient increase can be considered negligible, it not showing the expected increase of a rotor-diffuser system.